ANALISA PENGARUH WORK FAMILY-CONFLICT TERHADAP JOB EMBEDEDDNESS: JOB SATISFACTION SEBAGAI VARIABEL MEDIASI - AL Lya Razaq; Zaitul Zaitul; Sefnedi Sefnedi; Reni Yuliviona; Idham Khalil (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to analyze the influence of work-family conflict on the work engagement of government employees in the West Pasaman Regency Education Service. In addition, this research investigates the role of the variable job satisfaction as a mediating variable between work-family conflict and work engagement. Four hypotheses were developed and tested using a quantitative approach. Theory. The theory used in research is resource conservation theory. Research data is primary data collected using survey methods. The variable is measured using a five-point Likert scale with a range of strongly disagree (1) to strongly agree (5). The data processing method uses a structural equation model by applying Smart-Partial Least Square (PLS) 3.0 software. The final sample size was 30 respondents. Measurement models and structural assessment models are used to obtain research results. After passing the measurement model assessment, the structural model shows that the model has relevance and good predictive power. Hypothesis testing shows that job satisfaction mediates the relationship between work family conflict and job embeddedness with the mediation type Indirect-only mediation or full mediation. Apart from that, the research results also show that two direct influences are also significant, namely (i) the influence of work family conflict and job satisfaction, (ii) job satisfaction and job embeddedness.